298 MPACT OF GUIDELINES-ORIENTED AGE CUT-OFF IN INTERMEDIATE TO LOWVRISK PATIENTS UNDERGOING TRANSCATHETER AORTIC VALVE REPLACEMENT WITH NEWEST GENERATION SELF-EXPANDING VALVES: A COMBINED ANALYSIS FROM NEOPRO AND NEOPRO-2 REGISTRIES. (15th December 2022) - Sticchi, Alessandro; Gitto, Mauro; Pagnesi, Matteo; Baggio, Sara; Scotti, Andrea; Barbanti, Marco; Costa, Giuliano; Adamo, Marianna; Di Marco, Federico; Casenghi, Matteo; Lunardi, Mattia; Regazzoli, Damiano; et al.
Abstract: Introduction: While randomized controlled trials have widely shown superiority or non-inferiority of transcatheter aortic valve replacement (TAVR) across the whole spectrum of surgical risks, 2021 ESC guidelines on valvular heart disease provide a class Ia indication for TAVR for patients at high surgical risk or, alternatively, aging >=75 years, irrespective of their surgical risk. Conversely, for patients aging <75 y and at low risk, surgical aortic valve replacement is recommended. Thus, in intermediate-low (IL) risk patients, the 75 y age cut-off is pivotal to guide the choice of intervention. The aim of the present study was to explore the impact on such cut-off on clinical outcomes in a real-world setting. Methods: Consecutive IL surgical risk patients enrolled in the NEOPRO and NEOPRO-2 registries were included. A 1:1 propensity score matching (PSM) was used to match patients aged >= vs. <75 years old. The primary endpoint was the composite of all-cause death or cardiovascular hospitalizations. Results: A total of 3642 patients undergoing TAVR with self-expanding transcatheter heart valves (THVs) from 2012 to 2021 were enrolled. After PSM, 484 patients (N=242 in both groups) were included in the final analysis. Mean age was 70.1±5.2 in patients aged <75 y and 81.56±4.18 in those aged >=75 y (p<0.001), while mean Society of Thoracic Surgeon (STS) score was 3.6±2.5%. Implanted THVs were Acurate Neo, Evolut Pro, Acurate Neo 2 and Evolut Pro+ in 199 (41.1%), 188 (38.8%), 73 (15.1%) and 24 (5%) patients respectively, with no between-groups differences. Rates of in-hospital complications were comparable across the two age categories. At 1-year follow-up, the cumulative incidence of all-cause death was 11% in patients aged >=75 y and 13% in those aged <75y (Log-Rank p=0.627); similarly, the composite of all-cause death or cardiovascular hospitalizations occurred in 14% vs. 16% of patients (Log-Rank p=0.554). Conclusions: TAVI has comparable benefit across age strata in IL risk patients. The age cut-off suggested by current guidelines is not predictive of adverse events during hospital stay, neither of all-cause mortality through a mid-term follow-up. This opens the question to future studies focusing on lifetime management and not age cut-off.